436 PARADOXICAL RESPONSE OF URINE ALBUMIN EXCRETION ASSOCIATED WITH ORAL GLUCOSE CHALLENGE IN TYPE 2 DIABETES. Issue 1 (1st January 2007) - Gu, W.; Deedwania, P. C.; Peterson, M. W.
Abstract : Purpose: Microalbuminuria is strongly predictive of diabetic nephropathy and associated with increased cardiovascular morbidity and mortality. Little information is available regarding the relationship between postprandial hyperglycemia and microalbuminuria. We sought to determine the changes in urinary albumin excretion (Ualb) before and after a standard oral glucose loading. Methods: Fifty diabetic patients in a VA primary care clinic were recruited. Excluded were those with symptomatic heart diseases, chronic inflammatory conditions, blood pressure (BP) > 140/90 mm Hg, fasting blood glucose > 250 mg/dL, and glycated hemoglobin (HbA1c ) > 9%. Ualb values were determined in fasting state, at 2 and 6 hours after 75 g of glucose jelly. Other measured parameters included BP, body mass index (BMI), glucose, HbA1c, lipid panel, renal and hepatic functions, and highly sensitive C reactive protein (hs-CRP). ANOVA and linear multiple regression model were used for statistical analysis. Results: There were 12 (24%) smokers and 48 (96%) males, with a mean age of 67 years, BMI 28.5 kg/m 2, systolic BP 130 mm Hg, HbA1c 7.4%, and creatinine 1.04 mg/dL. Sixty eight percent of the patients were on statin, 68% on ACE-I/ARB, and 10% on insulin. Ualb at baseline and 2 and 6 hours post-glucose challenge were 71, 58, and 73 mg/L, respectively. Compared with the fasting level, 2 hours postglucose Ualb was significantly decreased ( p = .028 in quadratic trends) and returned to baseline in 6 hours. There were no significant associations between the changes in Ualb and other measured parameters and use of tobacco, statin, or ACE-I/ARB. Conclusion: Contrary to the common postulation that short-term hyperglycemia can cause transient elevations in Ualb, our result from this study population shows a decreased Ualb 2 hours after a glucose load. We propose the term paradoxical phenomenon . This may reflect glomerular self-protection and homeostasis in response to acute hyperglycemia. Possible mechanisms may involve glomerular osmotic or vascular changes through neuroendocrine regulation. The involvement of rennin-angiotensin system or inflammation cannot be excluded based on this study with a limited sample size and selected patient population. However, our preliminary results merit further investigation of potential mechanisms for this paradoxical phenomenon.